MASTERING TASKS OF ENGINEERING GRAPHICS THROUGH AUTOCAD SOFTWARE - U.T. Rikhsiboyev (Scholars Digest Publishing, 2023)
If we recognize the changes in the field of education today, one of our first problems is to expand students' worldview and increase their interest in science. At the same time, this article describes the method of developing students' attitude to science.
Keywords: command, Editing sequence, object, toolbar, mastery indicator, interest.